Insulin-Like Peptides Regulate Feeding Preference and Metabolism in Drosophila - Semaniuk, Uliana V.; Gospodaryov, Dmytro V.; Feden'ko, Khrystyna M.; Yurkevych, Ihor S.; Vaiserman, Alexander M.; Storey, Kenneth B.; Simpson, Stephen J.; Lushchak, Oleh (Frontiers in Physiology, 2018)
Fruit flies have eight identified Drosophila insulin-like peptides (DILPs) that are involved in the regulation of carbohydrate concentrations in hemolymph as well as in accumulation of storage metabolites. In the present study, we investigated diet-dependent roles of DILPs encoded by the genes dilp1–5, and dilp7 in the regulation of insect appetite, food choice, accumulation of triglycerides, glycogen, glucose, and trehalose in fruit fly bodies and carbohydrates in hemolymph. We have found that the wild type and the mutant lines demonstrate compensatory feeding for carbohydrates. However, mutants on dilp2,3, dilp3, dilp5, and dilp7 showed higher consumption of proteins on high yeast diets. To evaluate metabolic differences between studied lines on different diets we applied response surface methodology. High nutrient diets led to a moderate increase in concentration of glucose in hemolymph of the wild type flies. Mutations on dilp genes changed this pattern. We have revealed that the dilp2 mutation led drop in glycogen levels independently on diet, lack of dilp3 led to dramatic increase in circulating trehalose and glycogen levels, especially at low protein consumption. Lack of dilp5 led to decreased levels of glycogen and triglycerides on all diets, whereas knockout on dilp7 caused increase in glycogen levels and simultaneous decrease in triglyceride levels at low protein consumption. Fruit fly appetite was influenced by dilp3 and dilp7 genes. Our data contribute to the understanding of Drosophila as a model for further studies of metabolic diseases and may serve as a guide for uncovering the evolution of metabolic regulatory pathways.